Dynamics of contacts between lamellae of fibroblasts: Essential role of the actin cytoskeleton - Gloushankova, N. A. (The National Academy of Sciences, 1998)
We investigated actin cytoskeletal and adhesion molecule dynamics during collisions of leading lamellae of nontransformed and oncogene-transformed fibroblasts. By using real-time video microscopy, it was found that during lamellar collision there was considerable overlapping of leading lamellae followed by subsequent retraction. Overlapping of nontransformed fibroblasts was accompanied by formation of β-catenin-positive contact structures organized into strands oriented parallel to the long axis of the cell that were associated with bundles of actin filaments. Maintenance of such cell–cell contact structures critically depended on the contractility of actin cytoskeleton, as inhibition of contractility with serum-free medium or 2,3-butanedione 2-monoxime (BDM) resulted in loss of strand formation. Strand formation was recovered when cells in serum-free medium were incubated with the microtubule inhibitor nocodazole, which is known to increase contractility. Oncogene-transformed fibroblasts reacted to collisions with responses similar to nontransformed fibroblasts but did not develop well-organized cell–cell contacts. A model is presented to describe how differences in the organization of the actin cytoskeleton could account for the structurally distinct responses to cell–cell contact by polarized fibroblastic cells versus nonpolarized epithelial cells.